ICTAC Kinetics Committee recommendations for analysis of multi-step kinetics - Vyazovkin, Sergey; Burnham, Alan K.; Favergeon, Loic; Koga, Nobuyoshi; Moukhina, Elena; Pérez-Maqueda, Luis A.; Sbirrazzuoli, Nicolas (Thermochimica acta, 2020)
•Recommendations are provided for kinetic analysis of multi-step processes.•Focus is on four most commonly used approaches to multi-step kinetic analysis.•Specific advices are offered for efficient usage of each approach. The present recommendations have been developed by the Kinetics Committee of the International Confederation for Thermal Analysis and Calorimetry (ICTAC). The recommendations provide guidance on kinetic analysis of multi-step processes as measured by thermal analysis methods such as thermogravimetry (TGA) and differential scanning calorimetry (DSC). Ways of detecting the multi-step kinetics are discussed first. Then, four different approaches to evaluation of kinetic parameters (the activation energy, the pre-exponential factor, and the reaction model) for individual steps are considered. The approaches considered include multi-step model-fitting as well as distributed reactivity, isoconversional, and deconvolution analyses. For each approach practical advice is offered on its effective usage. Due attention is also paid to the typical problems encountered and to the ways of resolving them. The objective of these recommendations is to help a non-expert with efficiently performing multi-step kinetic analysis and interpreting its results.